1977
DOI: 10.1002/art.1780200508
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ultrastructure of Rheumatoid Articular Cartilage

Abstract: Six rheumatoid articular cartilage specimens, which appeared grossly normal and were shown to be free of pannus when examined under the light microscope, were examined electron microscopically. For comparison, normal‐appearing cartilage specimens from 2 patients with meniscus injury and 2 with degenerative joint disease (DJD) were also examined. In all cases the normal‐appearing joint surface of rheumatoid cartilage was abnormal. Amorphous‐appearing material was present to a depth varying between 6 and 25 m̈m.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…Histologic analysis of joint damage in RA has resulted in the report of a similar observation (38). In addition, in humans, surface damage can be seen microscopically in areas that are macroscopically normal (39). We also noted this latter result with regard to the lack of observable gross pathology indicative of chronic immune synovitis, after intravenous administration of antiproteoglycan monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 59%
“…Histologic analysis of joint damage in RA has resulted in the report of a similar observation (38). In addition, in humans, surface damage can be seen microscopically in areas that are macroscopically normal (39). We also noted this latter result with regard to the lack of observable gross pathology indicative of chronic immune synovitis, after intravenous administration of antiproteoglycan monoclonal antibodies.…”
Section: Discussionsupporting
confidence: 59%
“…While large numbers of PMN are present in rheumatoid synovial fluid, it is generally agreed that PMN are not present in significant numbers on the pannus-free surface of cartilage (10) or in the rheumatoid pannus itself (13). However, it has recently been reported that large numbers of PMN are present at the pannus-cartilage junction (14) and also that some PMN are present on the surface of rheumatoid cartilage (1 1); this suggests that these cells may participate in rheumatoid cartilage destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for this is based on the presence of humoral and cellular immunity to these elements in patients as well as their arthritogenic potenlial in animal models of arthritis [1][2][3], Chondrocytes produce and maintain cartilage matrix and whilst humoral [4] and cellular [5] re.sponses to chondrocytes have been reported in both osteoarthritis (OA) and rheumatoid arthritis (RA), their role in these conditions is not clear. Ultrastructural studies of rheumatoid articular eartilage have demonstrated cartilage degradation in areas free of pannus tissue [6] and immunohistochemical studies of the cartilage pannus junction in RA suggest that some ofthe fibroblast-like cells identified in this important region may be of ehondrocytc origin [7,8], Other studies ofthis region have shown MHC class II bearing cells whieh also demonstrate intracellular CIL a cartilage specific collagen [9]. The nature of these eells is unknown but il is speculated that they are phagocytes flO].…”
Section: Introductionmentioning
confidence: 99%